Utilization of Turkish Chromite Tailings in the Manufacturing of Building Bricks - Bayat, O.; Vapur, H. (Asian Journal of Chemistry, 2016)
This paper concerns with the building bricks made with chromite tailings material which mainly consists SiO2 and MgO. In chromite mining large amounts of clay containing tailing have to be discarded. The chromite tailings in mineral processing do not only cause economical loss but also bring about serious environmental problems. In order to solve this problem, the possibility of using chromite tailings in red brick manufacturing was investigated. Physical properties of the bricks made with the tailings were similar with the control bricks. The compressive strength increased upto 405 kg/cm2 with an addition of 20% tailings in comparison with reference bricks having 380 kg/cm2 on compressive strength.